Formaldehyde 2% is not a useful means of detecting allergy to formaldehyde releasers: results of the ESSCA network, 2015-2018 - Whitehouse, Heather; Uter, Wolfgang; Geier, Johannes; Ballmer-Weber, Barbara; Bauer, Andrea; Cooper, Susan; Czarnecka-Operacz, Magdalena; Dagmar, Simon; Dickel, Heinrich; Fortina, Anna Belloni; Gallo, Rosella; Giménez-Arnau, Ana M.; et al. (Contact dermatitis, 2021)
Background Studies suggest that patch testing with formaldehyde releasers (FRs) gives significant additional information to formaldehyde 1% aq. and should be considered for addition to the European baseline series (EBS). It is not known if this is also true for formaldehyde 2% aq. Objectives To determine the frequency of sensitization to formaldehyde 2% aq. and co-reactivity with FRs. To establish whether there is justification for including FRs in the EBS. Materials and Methods A 4-year, multi-center retrospective analysis of patients with positive patch test reactions to formaldehyde 2% aq. and five FRs. Results A maximum of 15 067 patients were tested to formaldehyde 2% aq. and at least one FR. The percentage of isolated reactions to FR, without co-reactivity to, formaldehyde 2% aq. for each FR were: 46.8% for quarternium-15 1% pet.; 67.4% imidazolidinyl urea 2% pet.; 64% diazolidinyl urea 2% pet.; 83.3% 1,3-dimethylol-5, 5-dimethyl hydantoin (DMDM) hydantoin 2% pet. and 96.3% 2-bromo-2-nitropropane-1,3-diol 0.5% pet. This demonstrates that co-reactivity varies between FRs and formaldehyde, from being virtually non-existent in 2-bromo-2-nitropropane-1,3-diol 0.5% pet. (Cohen's kappa: 0, 95% confidence interval [CI] −0.02 to 0.02)], to only weak concordance for quaternium-15 [Cohen's kappa: 0.22, 95%CI 0.16 to 0.28)], where Cohen's kappa value of 1 would indicate full concordance. Conclusions Formaldehyde 2% aq. is an inadequate screen for contact allergy to the formaldehyde releasers, which should be considered for inclusion in any series dependant on the frequency of reactions to and relevance of each individual allergen.
"First published: 02 September 2020".- Frontdoor des Artikels
Gesehen am 05.09.2024